Identification, structural characterization, and in silico expression analysis of the sucrose transporter ‘SWEET’ gene family in peanut (Arachis hypogaea) - Ha Duc Chu; Quynh Thi Ngoc Le; Yen Hai Thi Hoang; Thu Phuong Pham; Hong Viet La; Nguyet Minh Thi Nguyen; Anh Xuan Duong; Thao Duc Le; Linh Hung Le; Hoi Xuan Pham (Vietnam Journal of Science, Technology and Engineering, 2020)
SWEET (Sugars Will Eventually be Exported Transporter) proteins are well known to play pivotal roles in the growth and development of plants. Here, we report the presence of 43 members of the AhSWEET family in peanut (Arachis hypogaea) and determine their general characteristics including chromosomal localization, gene structure, and numerous physical and chemical features of the proteins. We found that the AhSWEET genes were unevenly distributed among the peanut’s 20 chromosomes. The AhSWEET proteins were hydrophobic with a grand average hydropathicity >0 while a majority of the proteins were basic with isoelectric points >7.0. Additionally, most of the AhSWEET genes contained 6 exons and 5 introns. The expression profiles of the AhSWEET genes were explored based on the previous transcriptome atlas. Interestingly, we found that the AhSWEET genes exhibited differential expression patterns across various organs and tissues during the growth and development of peanut plants. Our study provides a solid foundation of the AhSWEET gene family for further functional characterization of AhSWEET genes in the regulation of peanut growth and development.